Cytotoxicity of some 1-(2,4-dihydroxyphenyl)-3-(4-phenylpiperidin-1-yl) prop-2-en-1-one derivatives using MTT assay - Farzaneh Fesahat; Mehdi Khoshneviszadeh; Alireza Foroumadi; Alireza Vahidi; Maryam Fereidounpour; Amirhossein Sakhteman (Shiraz University of Medical Sciences, 2015)
Some N-substituted piperidine structures were synthesized and evaluated for cytotoxic activity against four different cell lines using the standard MTT assay method and Doxorubicin was used as the reference drug. The result of cytotoxic activity as a measurement of IC50 values revealed that three of the synthesized compounds were active against breast cancer cell line. Compound 6a bearing hydroxyl at para position of piperidine ring was the most active compound within this series. The N-subtituted piperidine with propene substructure could be considered as a lead structure for further studies of structure activity relationship to develop more potent compounds in future.